A politics of the Performativity in Forming of the Gender Identity (JOURNAL OF ADVANCES IN LINGUISTICS, 2015)
This study is an attempt to examine the role of performativity in forming and determining gender identity in a society. This study included articles and books that were written about language, gender, identity of a gender and also politics of performativity. These studies were analyzed qualitatively and quantitatively. The result of these analyzing shows gender identity is not natural or innate. Rather it takes its meaning from the inside of a person. This formation is influenced by the thoughts and ideas of society about gender and identity. It is clear gender and also gender identity constructed by language, then language goes into behavior, it, finally, begins to shape peoples identities. It means that gender and identity of gender are formed and determined by language and behavior; peoples acts.